Implementing an Application Programming Interface for PROMIS Measures at Three Medical Centers - Bass, Michael; Oncken, Christian; McIntyre, Allison W.; Dasilva, Chris; Spuhl, Joshua; Rothrock, Nan E. (Applied Clinical Informatics, 2021)
Background There is an increasing body of literature advocating for the collection of patient-reported outcomes (PROs) in clinical care. Unfortunately, there are many barriers to integrating PRO measures, particularly computer adaptive tests (CATs), within electronic health records (EHRs), thereby limiting access to advances in PRO measures in clinical care settings.Objective To address this obstacle, we created and evaluated a software integration of an Application Programming Interface (API) service for administering and scoring Patient-Reported Outcomes Measurement Information System (PROMIS) measures with the EHR system.Methods We created a RESTful API and evaluated the technical feasibility and impact on clinical workflow at three academic medical centers.Results Collaborative teams (i.e., clinical, information technology [IT] and administrative staff) performed these integration efforts addressing issues such as software integration as well as impact on clinical workflow. All centers considered their implementation successful based on the high rate of completed PROMIS assessments (between January 2016 and January 2021) and minimal workflow disruptions.Conclusion These case studies demonstrate not only the feasibility but also the pathway for the integration of PROMIS CATs into the EHR and routine clinical care. All sites utilized diverse teams with support and commitment from institutional leadership, initial implementation in a single clinic, a process for monitoring and optimization, and use of custom software to minimize staff burden and error.
Keywords: electronic health records; implementation; computer adaptive algorithm; patient-reported outcomes; PROMIS